Modal parameter identification and seismic assessment of historical timber structures under near-fault and far-fault ground motions - Altunisik, Ahmet Can; Sunca, Fezayil; Sevim, Baris (ELSEVIER SCIENCE INC, 2023)
Timber, one of the oldest structural materials, is an essential material in the construction of traditional structures due to its undeniable advantages. However, wood is sensitive to environmental effects, and hence, historical timber structures experience various degradations and destructions during their service life. This highlights the necessity of investigating the structural responses of such structures using experimental techniques and cali-brated finite element models. This paper presents vibration-based system identification of two historical timber structures and an in-depth comparison of the effects of near-fault and far-fault ground motions on seismic re-sponses. Ambient vibration tests were carried out using the operational modal analysis method. Enhanced Frequency Domain Decomposition and Stochastic Subspace Identification methods were used for experimental modal parameters estimation. Also, the initial finite element models were calibrated considering the ambient vibration test results to correctly assess the seismic responses of the selected structures under near-fault and far-fault ground motions. The distributions of maximum amplitudes (displacements, internal forces, and absolute accelerations) under earthquake records with near-fault and far-fault are comparatively presented. All numerical results indicated that both near-fault ground motions and their far-fault counterparts played major roles in terms of the seismic responses of selected historical timber structures. In addition, these results illustrate that both had the potential to increase displacements and, internal forces at load-bearing elements, and leading to notable structural responses and destructive effects.
Keywords: Ambient vibration test; Historical timber structures; Modal parameters; Model updating; Near-fault and far-fault ground motion; STOCHASTIC SUBSPACE IDENTIFICATION; NONLINEAR DYNAMIC-RESPONSE; BRIDGES; PERFORMANCE; FREQUENCY; BEHAVIOR; DAMAGE; BUILDINGS; DESIGN; MODELS; Engineering